A copper alloy pipe and a production process and application thereof

CN122879547APending Publication Date: 2026-10-09JIANGXI PRO JIANGTONG LONGCHANG PRECISE COPPER PIPE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611238605.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-15
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]综上所述,现有技术仍存在以下不足:(1)D1依赖高比例特殊晶界和严格再结晶工艺,工艺窗口窄、设备要求高;(2)D2依赖特定化合物颗粒的数量和均匀性控制,工艺稳定性难以保证

Benefits of technology

本发明通过将Ni含量提升至0.2%-0.4%、Sn含量提升至0.15%-0.3%,构建了更致密的NiO+SnO2+Cu2O复合多层钝化膜。相比TP2单一的Cu2O薄膜,该复合钝化膜更加致密,能够有效阻挡甲酸根离子的渗透;同时,微量Fe(0.006%-0.020%)的添加可通过填充微小腐蚀隧道的方式,减少可溶性甲酸亚铜(CuHCOO)的富集,削弱歧化反应与氧化亚铜堆积产生的机械楔裂效应;经2.5%甲酸水溶液冷热交替腐蚀10天后,单管腐蚀最大深度≤155μm,远优于TP2铜管。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879547A_ABST
    Figure CN122879547A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of alloys, and particularly relates to a copper alloy pipe and a production process and application thereof. The copper alloy pipe is composed of the following components in percentage by mass: Ni 0.2%-0.4%, Sn 0.15%-0.3%, Fe 0.006%-0.02%, P 0.02%-0.04%, and the balance of Cu and inevitable impurities; wherein the mass ratio of Sn to Ni is 0.5-1. The process comprises the following steps: (1) batching and smelting -> (2) continuous casting -> (3) continuous rolling -> (4) joint drawing -> (5) disc drawing -> (6) on-line annealing -> (7) forming processing -> (8) horizontal winding -> (9) product annealing. The application significantly improves the formic acid corrosion resistance and high-temperature softening resistance of the copper alloy pipe, and has excellent mechanical properties and processing formability. The application can be used in the preparation of air conditioner heat exchanger materials, air conditioner indoor and outdoor machine connecting pipes, machine internal pipes or pipe assemblies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy technology, specifically relating to a copper alloy tube, its production process, and its application. Background Technology

[0002] As refrigeration equipment develops towards higher efficiency, energy saving, and miniaturization, higher requirements are placed on copper alloy materials used in heat exchangers and connecting piping. While traditional phosphorus-deoxidized copper (TP2) has good machinability, its strength and burst pressure are insufficient to meet the needs of modern high-pressure, thin-walled designs. To improve the strength of copper tubes, various high-strength copper alloy solutions have been proposed in existing technologies.

[0003] Patent document CN120648935A (hereinafter referred to as "D1") discloses a high-performance copper alloy tube and its preparation method. By adding Sn, Ni, and P elements to Cu and controlling the content and ratio of each element, and simultaneously introducing a high proportion of Σ3, Σ9, and Σ27 lattice grain boundaries through a recrystallization process, a copper alloy tube with high strength, high machinability, excellent pressure resistance, corrosion resistance, and high-temperature softening resistance is obtained. However, the core element Ni content in D1 ranges from 0.08% to 0.3%, and it relies on a specific recrystallization process (deformation ≥80% or 3-6 cycles) to achieve a high proportion of lattice grain boundaries (Σ3 / 9 / 27 total proportion ≥50%). This results in a relatively strict process window and high requirements for production equipment and process control.

[0004] Patent document CN119265448A (hereinafter referred to as "D2") discloses a copper alloy tube and its preparation method and application. By adding Zr, B, and Mn, and controlling the content of Zr, B, and Mn and the preparation process, the quantity and uniformity of MnZr and BMn compounds are regulated, thereby improving the tensile strength, elongation, corrosion resistance, and processing properties such as bending, flaring, welding, and pressure resistance of the copper alloy tube. The core of D2 lies in its reliance on specific MnZr and BMn compound particles (the number of MnZr compound particles on the cross-section is 0.005-0.15 particles / μm², and the number of BMn compound particles is 0.005-0.2 particles / μm²). 2 This method requires precise control of the number and distribution of compound particles, and places extremely high demands on the stability of the smelting and heat treatment processes.

[0005] In summary, the existing technologies still have the following shortcomings: (1) D1 relies on a high proportion of special grain boundaries and a strict recrystallization process, resulting in a narrow process window and high equipment requirements; (2) D2 relies on the control of the number and uniformity of specific compound particles, making it difficult to guarantee process stability. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a copper alloy tube and its production process. By optimizing the ratio range of Ni, Sn, Fe and P, and coordinating with specific continuous casting and rolling process control, the copper alloy tube's resistance to formic acid corrosion and high-temperature softening is significantly improved, while also possessing excellent mechanical properties and processability.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A copper alloy tube is composed of the following components in mass percentage: Ni 0.2%-0.4%, Sn 0.15%-0.3%, Fe 0.006%-0.02%, P 0.02%-0.04%, with the balance being Cu and unavoidable impurities; The mass ratio of Sn to Ni is 0.5-1. The copper alloy tube has a single face-centered cubic crystal structure α phase with no undesirable hard and brittle phase precipitation. The microstructure of the copper alloy tube has an equiaxed grain ratio of ≥85% and an average grain size of 15-25μm. After being subjected to alternating hot and cold corrosion in a 2.5% formic acid aqueous solution atmosphere for 10 days, the maximum corrosion depth of a single copper alloy tube is ≤155μm. After being kept at 800℃ for 1 hour, the tensile strength of the copper alloy tube decreased by ≤20%. The copper alloy tube is either an internally threaded tube or a plain tube.

[0008] In a preferred example, the composition consists of the following components in mass percentage: Ni 0.22%-0.28%, Sn 0.19%-0.22%, Fe 0.008%-0.012%, P 0.02%-0.04%, with the balance being Cu and unavoidable impurities.

[0009] In a preferred embodiment, the copper alloy tube has a tensile strength of 240-270 MPa, a yield strength of 75-95 MPa, and an elongation after fracture of ≥48%.

[0010] In a preferred embodiment, the copper alloy tube is an internally threaded tube with a spiral groove structure on its inner surface. The tooth height of the spiral groove is 0.12-0.18 mm and the apex angle is 35°-50°.

[0011] In a preferred embodiment, the copper alloy tube is a plain tube with an outer diameter of 5-20 mm and a wall thickness of 0.3-1.5 mm.

[0012] Based on a general inventive concept, another objective of this invention is to provide a production process for the aforementioned copper alloy tube, employing a continuous casting and rolling process, comprising the following steps: (1) Batching and smelting: Prepare electrolytic copper, pure nickel plate, pure tin plate, copper-iron alloy, and phosphorus copper master alloy according to the design composition; add electrolytic copper to the melting furnace and set the melting furnace temperature to 1175-1195℃; transfer the molten copper to the casting furnace and set the casting furnace temperature to 1140-1160℃. Before the molten copper is transferred into the casting furnace, the phosphor bronze master alloy is first added to the furnace chamber. Then, pure nickel plates and copper-iron alloys are wrapped in copper foil and added to the casting furnace. They are kept at a temperature of 15-20 minutes to allow the high-melting-point elements to dissolve completely. Then, pure tin plates are wrapped in copper foil and added to the casting furnace. (2) Continuous casting: The homogenized copper liquid is horizontally continuously cast with a traction speed of ≤390mm / min, a primary cooling water flow rate of 15-70L / min, and a secondary cooling water flow rate of 30-80L / min to obtain a continuous casting tube blank. (3) Continuous rolling: The continuously cast tube billet is subjected to planetary rolling at a rolling speed of 1.9-2.0 m / min to obtain a rolled tube billet with an outer diameter of 51-55 mm and a wall thickness of 2.3-2.7 mm; (4) Continuous stretching: The rolled tube blank is subjected to diameter reduction stretching at a speed of 10-80m / min, reducing the outer diameter of the rolled tube blank to 20-28mm and the wall thickness to 1-1.4mm, to obtain an intermediate tube blank; (5) Coil drawing: The intermediate tube blank after the joint drawing is continuously drawn 8-9 times, the drawing speed is 8-13m / s, and the total deformation is 85-93%; (6) Online annealing: The tube blank after coiling is subjected to online annealing and softening treatment. The annealing speed is ≤400m / min and the tube blank exit temperature is 970-1010℃. (7) Forming process: When preparing internally threaded tubes, the tube blank after online annealing is spun into internal threads. The spinning speed is 15000-35000 r / min and the stretching speed is 40-60 m / min. When preparing plain tubes, the spinning step is omitted and other conditions are the same as those for preparing internally threaded tubes. (8) Horizontal winding: The formed tube blank is horizontally wound at a speed of 250-350m / min to obtain a coil with a winding height of 200-400mm; (9) Finished product annealing: The coil obtained by horizontal winding is subjected to recrystallization annealing at a temperature of 500-580℃ and a holding time of 35-45min to obtain copper alloy tube.

[0013] In a preferred example, in step (1), the pure nickel plate is in the form of a 30×30×5mm block, weighing 40g / block.

[0014] In a preferred example, in step (2), the traction speed of the horizontal continuous casting is 380-390 mm / min, the primary cooling water flow rate is 45-55 L / min, and the secondary cooling water flow rate is 60-70 L / min.

[0015] In a preferred example, in step (3), the feed rate of planetary rolling is 1.9-2.0 m / min, self-heating rolling is achieved by utilizing deformation heat, and the exit temperature is 750-850℃.

[0016] In a preferred example, in step (3), the temperature of the primary cooling water in the continuous rolling process is controlled to be 35-45℃; below 35℃, recrystallization is insufficient, and above 45℃, surface oxidation occurs.

[0017] In a preferred example, in step (3), the frequency of polishing and maintaining the rolls in the continuous rolling process is adjusted from the usual (once every 24 hours) to once every 12 hours.

[0018] In a preferred example, in step (5), the drawing speed of the intermediate pass is controlled at 12-13 m / s, and the drawing speed of the finished pass is controlled at 8-10 m / s.

[0019] In a preferred example, in step (7), during the internal thread spinning process, the spinning ratio is 520 r / m.

[0020] Technically related to the inventive concept of this invention is the application of the aforementioned copper alloy tube in the manufacture of air conditioning heat exchange equipment, connecting piping between indoor and outdoor air conditioning units, internal piping, or pipe assemblies.

[0021] Compared with the prior art, the advantages and positive effects of the present invention are as follows: (1) Significantly improved corrosion resistance This invention constructs a denser NiO+SnO2+Cu2O composite multilayer passivation film by increasing the Ni content to 0.2%-0.4% and the Sn content to 0.15%-0.3%. Compared to the single Cu2O film of TP2, this composite passivation film is denser and can effectively block the penetration of formate ions. At the same time, the addition of trace amounts of Fe (0.006%-0.020%) can reduce the enrichment of soluble cuprous formate (CuHCOO) by filling micro-corrosion tunnels, thus weakening the mechanical wedging effect caused by disproportionation reaction and cuprous oxide accumulation. After 10 days of alternating hot and cold corrosion with 2.5% formic acid aqueous solution, the maximum corrosion depth of a single tube is ≤155μm, which is far superior to that of TP2 copper tubes.

[0022] (2) Significantly improved resistance to high-temperature softening This invention raises the annealing temperature of the finished product to 500-580℃ (preferably 580℃). Through the optimization of the stepped heating annealing process, the tensile strength reduction rate of the copper tube after holding at 800℃ for 1 hour is ≤20%. The higher annealing temperature of the finished product, combined with the optimized composition, enables the alloy to obtain better thermal stability, effectively overcoming the technical problem of the significant decrease in the intrinsic strength of thin-walled copper tubes under high temperature environment.

[0023] (3) Excellent mechanical properties and processability The copper alloy tube of this invention has a tensile strength of 240-270 MPa, a yield strength of 75-95 MPa, and an elongation after fracture of ≥48%, exhibiting both high strength and good plasticity. The average grain size in the microstructure is 15-25 μm, with an equiaxed grain ratio of ≥85%, providing a microstructure basis for excellent machinability. It also meets all machinability requirements, including bending and flaring.

[0024] (4) Significant differences from existing technologies Compared to D1 (CN120648935A), this invention does not rely on a high proportion of Σ3 / 9 / 27 lattice grain boundaries (D1 requires ≥50%) to achieve performance targets. Instead, it achieves comprehensive performance improvement through a composite mechanism of "solid solution strengthening + grain refinement strengthening + tunnel filling," representing a completely different technical path. This invention shifts the Ni content range upwards, with a higher upper limit, forming a unique synergistic corrosion resistance and high-temperature softening resistance mechanism with Sn and Fe elements. Simultaneously, this invention has a narrower annealing temperature range and shorter holding time, eliminating the need for the cyclic recrystallization process found in D1. This process window is more suitable for industrial mass production, and combined with the specific component ratios of this invention, forms a completely new technical solution.

[0025] Compared to D2 (CN119265448A), this invention does not add Zr, B, or Mn elements, nor does it rely on specific MnZr and BMn compound particles for reinforcement. Instead, it achieves performance improvement through the synergistic effect of four elements: Fe, Ni, Sn, and P. This invention innovatively introduces trace amounts of Fe (0.006%-0.020%) as a functional corrosion-resistant component, utilizing its "tunneling" effect to enhance corrosion resistance—a technical feature not addressed in D1 and D2. Attached Figure Description

[0026] Figure 1 Metallographic image of the microstructure of the copper alloy internally threaded tube prepared in Example 1 of the present invention.

[0027] Figure 2 The images show a comparison of the cross-sectional morphology of the copper tubes after formic acid corrosion in Comparative Example 1 and Example 1. In Comparative Example 1 (TP2) after formic acid corrosion, (a) shows the cross-sectional morphology of the copper tubes after formic acid corrosion, and (b) shows the cross-sectional morphology of the copper alloy internally threaded tubes after formic acid corrosion.

[0028] Figure 3 The electrochemical polarization comparison curves are for comparison between Example 1 and Example 2. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is further described in conjunction with specific embodiments. However, this invention is not limited to these embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. Unless otherwise specified, the raw materials used in this invention are all commercially available industrial pure or intermediate alloys, and the equipment used is all conventional commercially available equipment in the field of alloy processing, without any special customization requirements. Experimental methods in the embodiments that do not specify specific conditions are all carried out according to conventional conditions in the art or conditions provided by the manufacturer.

[0030] The specific embodiments of the present invention will be described in detail below.

[0031] Example 1

[0032] A copper alloy internally threaded pipe, the composition by mass percentage is: Ni 0.25%, Sn 0.22%, Fe 0.010%, P 0.028%, with the balance being Cu and unavoidable impurities.

[0033] The preparation process is as follows: (1) Batching and smelting: Prepare electrolytic copper (purity ≥99.98%), pure nickel plate (30×30×5mm block, 40g / block), pure tin plate, copper-iron alloy (Cu-10%Fe), and phosphorus copper master alloy (Cu-14%P) according to the design composition; add electrolytic copper to the melting furnace, and set the melting furnace temperature to 1185℃; transfer the molten copper to the casting furnace, and set the casting furnace temperature to 1155℃; Before the molten copper is transferred into the casting furnace, the phosphor bronze master alloy is first added to the furnace chamber. Then, pure nickel plates and copper-iron alloys are wrapped in copper foil and added to the casting furnace. They are kept at a temperature of 15-20 minutes to allow the high-melting-point elements to dissolve completely. Then, pure tin plates are wrapped in copper foil and added to the casting furnace. (2) Continuous casting: The homogenized copper liquid is horizontally continuously cast, the traction speed is controlled at 380 mm / min, the primary cooling water flow rate is 50 L / min, the secondary cooling water flow rate is 65 L / min, and a continuous casting tube blank with an outer diameter φ of 90 mm and a wall thickness of 15 mm is obtained. (3) Continuous rolling: The continuously cast tube billet is subjected to planetary rolling at a rolling speed of 1.9 m / min to obtain a rolled tube billet with an outer diameter φ of 53 mm and a wall thickness of 2.5 mm; the temperature of the primary cooling water is controlled at 40℃ in this process; the frequency of polishing and maintenance of the rolls is once per shift. (4) Continuous stretching: The rolled tube blank is subjected to diameter reduction stretching at a speed of 60m / min, reducing the outer diameter of the rolled tube blank to 26mm and the wall thickness to 1.3mm to obtain an intermediate tube blank; (5) Coil drawing: The intermediate tube blank after the joint drawing is continuously drawn in 9 passes. The drawing speed of the intermediate passes is controlled at 12m / s, and the drawing speed of the finished product passes is controlled at 9m / s. The outer diameter φ of the finished tube is 9.52mm, the wall thickness is 0.31mm, and the total section shrinkage rate is 91%. (6) Online annealing: The tube blank after coiling is subjected to online annealing and softening treatment. The annealing speed is 350m / min and the tube blank exit temperature is 980℃. (7) Internal thread spinning: The tube blank after online annealing is fed into the spinning machine. The spinning speed is 26000r / min, the stretching speed is 50m / min, and the spinning ratio is 520r / m. A spiral groove (tooth height 0.15mm, apex angle 45°) is formed on the inner wall of the tube. (8) Horizontal winding: The formed tube blank is horizontally wound at a winding speed of 300m / min to obtain a coil with a winding height of 300mm; (9) Finished product annealing: The coil is placed in an annealing furnace for recrystallization annealing. The annealing temperature is 580℃ and the holding time is 40min. Then it is cooled to room temperature with the furnace to obtain the final copper alloy tube finished product.

[0034] The performance of the copper alloy internally threaded tube prepared in this embodiment was tested, and the results are shown in Table 1 below.

[0035] Example 2

[0036] The only difference between this embodiment and Embodiment 1 is that the Ni content is adjusted to 0.30%, the Sn content to 0.25%, and the Fe content to 0.015%; the annealing temperature of the finished product is adjusted to 560℃, and the holding time is 40min. The remaining processes are the same as in Example 1. The performance test results are shown in Table 1 below.

[0037] Example 3

[0038] The only difference between this embodiment and Embodiment 1 is that the Ni content is adjusted to 0.20%, the Sn content to 0.18%, and the Fe content to 0.008%; the annealing temperature of the finished product is adjusted to 540℃, and the holding time is 45min. The remaining processes are the same as in Example 1. The performance test results are shown in Table 1 below.

[0039] Comparative Example 1

[0040] A commercially available TP2 phosphorus-deoxidized copper tube (composition: P 0.028%, balance Cu), with a specification of φ9.52mm × 0.31mm internal thread, was used as a comparison sample. The performance test results are shown in Table 1 below.

[0041] Comparative Example 2

[0042] Copper alloy tubes with internal threads, φ9.52mm × 0.31mm, were prepared according to the composition (Sn 0.36%, Ni 0.10%, P 0.031%) of Example 2 in patent document CN120648935A (D1) and a single recrystallization process (total deformation of 88.1% during coil drawing, and annealing of the finished product at 580℃ / 90min). The performance test results are shown in Table 1 below.

[0043] Performance testing

[0044] The copper alloy tubes of Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, and the test methods are as follows: 1. Tensile mechanical properties: Tested according to GB / T 228.1-2010, with a gauge length of 50 mm, a tensile speed of 5 mm / min, and the average value of 3 parallel specimens.

[0045] 2. Grain size and microstructure: Tests were conducted according to GB / T 6394-2017, and the proportion of equiaxed grains and the average grain size within the field of view were statistically analyzed.

[0046] 3. Bending performance: According to GB / T 244-2008, bend the tube 180° with the mandrel diameter being 1.5 times the outer diameter of the tube, and observe whether cracks appear on the surface.

[0047] 4. Flaring performance: In accordance with Appendix C of GB / T 17791-2017, a 60° punching cone is used, with a flaring rate of 40%.

[0048] 5. Bursting pressure: The hydraulic burst test shall be carried out in accordance with GB / T 241-2007. The calculation method of the burst pressure attenuation rate after welding is: (original pipe burst pressure - post-weld burst pressure) / original pipe burst pressure × 100%.

[0049] 6. Corrosion resistance: A 2.5% (v / v) formic acid aqueous solution was used. The test involved immersion at 50°C for 12 hours and standing at room temperature for 12 hours as one cycle, followed by alternating hot and cold corrosion for 10 days. The solution was changed every 3 days during the test. The sample was suspended vertically 20 mm below the solution surface. After the corrosion was completed, a cross-sectional sample was prepared, and the maximum corrosion depth of the cross-section was measured.

[0050] 7. High-temperature softening resistance: The finished annealed sample was placed at 800℃ for 1 hour and then air-cooled to test its tensile strength; the tensile strength decay rate was calculated as: (original tensile strength - tensile strength after high-temperature treatment) / original tensile strength × 100%, where the original tensile strength is the tensile strength of the finished annealed sample.

[0051] The results are shown in Table 1 below.

[0052]

[0053] The test results show that: (1) Corrosion resistance The maximum corrosion depth of 2.5% formic acid in Examples 1-3 was 142-155 μm, significantly better than Comparative Example 1 (TP2, 215 μm) and Comparative Example 2 (D1 process, 165 μm). Among them, Example 2 (Ni 0.30%, Sn 0.25%, annealed at 580℃ for 40 min) had the lowest corrosion depth (142 μm), which was about 34% lower than TP2, about 14% lower than D1 process, and about 23% lower than the previous generation scheme. This shows that by increasing the Ni content to 0.20%-0.40% and the Sn content to 0.15%-0.30%, the present invention constructs a denser composite passivation film, significantly improving corrosion resistance.

[0054] (2) Resistance to high temperature softening The tensile strength decay rate of Examples 1-3 after holding at 800℃ for 1 hour was 13%-16%, significantly better than Comparative Example 1 (32%) and Comparative Example 2 (19%). Among them, the decay rate of Example 2 (580℃×40min) was only 13%, indicating that the higher annealing temperature combined with the optimized composition resulted in superior thermal stability of the alloy. It is worth noting that although Comparative Example 2 (D1 process) also exhibited a low decay rate of 19%, it relied on a high proportion of Σ3 / 9 / 27 lattice grain boundaries (≥50%), resulting in a strict process window. This invention achieves comparable high-temperature softening resistance without relying on special grain boundaries, and has wider process adaptability.

[0055] (3) Mechanical properties and processability Examples 1-3 exhibit tensile strengths of 252-265 MPa, yield strength ratios of 0.32-0.35, and elongation after fracture of 48%-52%, balancing high strength and good plasticity. The average grain size in the microstructure is 15-18 μm, with an equiaxed grain ratio of 88%-91%, providing a microstructure basis for excellent processing performance. Bending and flaring properties are all satisfactory, demonstrating excellent machinability. Compared to Comparative Example 2 (process D1), the present invention has a higher equiaxed grain ratio (88%-91% vs 62%) and better microstructure uniformity, which is beneficial for uniform deformation during processing.

[0056] (5) Optimal solution Example 2 (Ni 0.30%, Sn 0.25%, Fe 0.015%, P 0.028%, annealed at 580℃ for 40min) achieved the best balance between corrosion resistance (142μm), high-temperature softening resistance (attenuation rate 13%), and comprehensive mechanical properties, and is the preferred solution of the present invention.

[0057] (5) Industrial applicability The high-strength, corrosion-resistant copper alloy tube of this invention can be widely used in air conditioning heat exchangers, refrigeration connection piping, and various high-pressure, thin-walled heat exchange equipment. Its excellent corrosion resistance, high-temperature softening resistance, and processability effectively meet the stringent requirements of new refrigerants (such as CO2) for high pressure resistance and long service life of copper tube materials. The production process of this invention can be implemented using existing continuous casting and rolling production lines without large-scale equipment modifications, and it has good industrial application value.

[0058] The above embodiments are merely preferred embodiments of the present invention. Any simple modifications, alterations, and substitutions made to the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A copper alloy tube, characterized in that, The copper alloy tube is composed of the following components by mass percentage: Ni 0.2%-0.4%, Sn 0.15%-0.3%, Fe 0.006%-0.02%, P 0.02%-0.04%, with the balance being Cu and unavoidable impurities; wherein the mass ratio of Sn to Ni is 0.5-1; the copper alloy tube has a single face-centered cubic α-phase crystal structure; in the microstructure of the copper alloy tube, the proportion of equiaxed grains is ≥85%, and the average grain size is 15-25 μm; After being subjected to alternating hot and cold corrosion in a 2.5% formic acid aqueous solution atmosphere for 10 days, the maximum corrosion depth of a single copper alloy tube is ≤155μm; after being kept at 800℃ for 1 hour, the tensile strength reduction rate of the copper alloy tube is ≤20%. The copper alloy tube is either an internally threaded tube or a plain tube.

2. The copper alloy tube according to claim 1, characterized in that, It is composed of the following components in mass percentage: Ni 0.22%-0.28%, Sn 0.19%-0.22%, Fe 0.008%-0.012%, P 0.02%-0.04%, with the balance being Cu and unavoidable impurities.

3. The copper alloy tube according to claim 1, characterized in that, The copper alloy tube has a tensile strength of 240-270 MPa, a yield strength of 75-95 MPa, and an elongation after fracture of ≥48%.

4. The copper alloy tube according to claim 1, characterized in that, The copper alloy tube is an internally threaded tube with a spiral groove structure on its inner surface. The tooth height of the spiral groove is 0.12-0.18 mm and the apex angle is 35°-50°.

5. The copper alloy tube according to claim 1, characterized in that, The copper alloy tube is a plain tube with an outer diameter of 5-20 mm and a wall thickness of 0.3-1.5 mm.

6. A manufacturing process for a copper alloy tube as described in any one of claims 1-5, characterized in that, The continuous casting and rolling process is adopted, including the following steps: (1) Batching and smelting: Prepare electrolytic copper, pure nickel plate, pure tin plate, copper-iron alloy, and phosphorus copper master alloy according to the design composition; add electrolytic copper to the melting furnace and set the melting furnace temperature to 1175-1195℃; transfer the molten copper to the casting furnace and set the casting furnace temperature to 1140-1160℃. Before the molten copper is transferred into the casting furnace, the phosphor bronze master alloy is first added to the furnace chamber. Then, pure nickel plates and copper-iron alloys are wrapped in copper foil and added to the casting furnace chamber, held at the temperature for 15-20 minutes, and then pure tin plates are wrapped in copper foil and added to the casting furnace chamber. (2) Continuous casting: The homogenized copper liquid is horizontally continuously cast with a traction speed of ≤390mm / min, a primary cooling water flow rate of 15-70L / min, and a secondary cooling water flow rate of 30-80L / min to obtain a continuous casting tube blank. (3) Continuous rolling: The continuously cast tube billet is subjected to planetary rolling at a rolling speed of 1.9-2.0 m / min to obtain a rolled tube billet with an outer diameter of 51-55 mm and a wall thickness of 2.3-2.7 mm; (4) Continuous stretching: The rolled tube blank is subjected to diameter reduction stretching at a speed of 10-80m / min, reducing the outer diameter of the rolled tube blank to 20-28mm and the wall thickness to 1-1.4mm, to obtain an intermediate tube blank; (5) Coil drawing: The intermediate tube blank after the joint drawing is continuously drawn in 8-9 passes, with a drawing speed of 8-13 m / s and a total deformation of 85-93%; (6) Online annealing: The tube blank after coiling is subjected to online annealing and softening treatment. The annealing speed is ≤400m / min and the tube blank exit temperature is 970-1010℃. (7) Forming process: When preparing internally threaded tubes, the tube blank after online annealing is spun into internal threads. The spinning speed is 15000-35000 r / min and the stretching speed is 40-60 m / min. When preparing plain tubes, the spinning step is omitted and other conditions are the same as those for preparing internally threaded tubes. (8) Horizontal winding: The formed tube blank is horizontally wound at a speed of 250-350m / min to obtain a coil with a winding height of 200-400mm; (9) Finished product annealing: The coil obtained by horizontal winding is subjected to recrystallization annealing at a temperature of 500-580℃ and a holding time of 35-45min to obtain copper alloy tube.

7. The production process according to claim 6, characterized in that, In step (2), the traction speed of the horizontal continuous casting is 380-390 mm / min, the primary cooling water flow rate is 45-55 L / min, and the secondary cooling water flow rate is 60-70 L / min.

8. The production process according to claim 6, characterized in that, In step (3), the feed rate of planetary rolling is 1.9-2.0 m / min and the outlet temperature is 750-850℃.

9. The production process according to claim 6, characterized in that, In step (3), the temperature of the primary cooling water in the continuous rolling process is controlled to be 35-45℃.

10. The production process according to claim 6, characterized in that, In step (5), the drawing speed of the intermediate passes is controlled at 12-13 m / s, and the drawing speed of the finished passes is controlled at 8-10 m / s.

11. The production process according to claim 6, characterized in that, In step (7), during the internal thread spinning process, the spinning ratio is 520r / m.

12. The application of the copper alloy tube according to any one of claims 1-5 in the manufacture of air conditioning heat exchange equipment, air conditioning indoor and outdoor unit connecting piping, internal piping or pipe assembly.

Citation Information

Patent Citations

  • Copper alloy pipe and preparation method and application thereof

    CN119265448A

  • High-performance copper alloy pipe and preparation method thereof

    CN120648935A